The Enigma of Being Yourself: A Critical Examination of the Concept of Authenticity. Issue 1 (March 2019) - Jongman-Sereno, Katrina P.; Leary, Mark R.
As the term is typically used, authenticity refers to the degree to which a particular behavior is congruent with a person's attitudes, beliefs, values, motives, and other dispositions. However, researchers disagree regarding the best way to conceptualize and measure authenticity, whether being authentic is always desirable, why people are motivated to be authentic, and the nature of the relationship between authenticity and psychological well-being. In this article, we examine existing views of authenticity, identify questionable assumptions about the concept of authenticity, and discuss issues regarding subjective feelings of inauthenticity, the implications of authenticity for psychological and social well-being, and the importance that people place on being authentic.